A systematic review of psychodynamic theories in community psychology: Discovering the unconscious in community work. Issue 6 (15th July 2020) - Caputo, Andrea; Tomai, Manuela
Abstract: The aim of this systematic review is to provide a narrative synthesis of the peer‐reviewed literature regarding the role of psychodynamics in community psychology. The authors screened 301 records on the topic, found in major citation databases (Scopus and Web of Science) without time or language restrictions. Ten articles addressing the review question were identified, showing the contributions of interpersonal psychoanalysis, Adlerian psychology, the Tavistock psychodynamic model, and Lacanian psychoanalysis. Several points of synergy between community psychology and psychodynamics were outlined mainly concerning empowerment theory, preventative and ecological perspective, power, and social order. Besides, the view on the community life, the role of emotion, and the conceptualization of the unconscious domain are discussed. Implications for community interventions are highlighted, regarding clients' demands, the role of community practitioners, and the use of transference/countertransference in consultative work. Limitations and future directions are also considered.